Analisis identitas nasional dalam film komang - Faritzky Mahartadi, Andi Al (Maliki Interdisciplinary Journal, 2025)
This research aims to analyze the representation of national identity in the film Komang, a movie that tells a cross-cultural story between two characters from different backgrounds: Raim from Buton and Ade (Komang) from Bali. Through a descriptive qualitative approach and content analysis method, this study examines elements of national identity reflected in the language, culture, and social values displayed throughout the film. The results of the analysis indicate that the film Komang successfully represents national values such as tolerance, harmony, and cultural integration through the interaction between characters and the use of regional languages. Raim embodies Butonese values that uphold traditions, Islam, and the principle of Bhinci-bhinciki kuli, while Komang reflects Balinese local wisdom rooted in the philosophy of Tri Hita Karana. Their interactions demonstrate a process of social and linguistic integration that strengthens the spirit of unity in diversity. This film serves as a concrete example that entertainment media can play a crucial role in shaping national identity awareness and educating the public about the importance of preserving culture and national values in the era of globalization.